New Left Encounters with Marx - Howard, Dick (Veritas (Porto Alegre), 2018)
The article uses the ideal of a New Left to conceptualize the underlying unity of diverse political experiences during the past half century. Although Marx is not the direct object of this reconstruction, his specter is a recurring presence at those “nodal points” where the imperative to move to “another element” becomes apparent. These are moments when the spirit that has animated a movement can advance no further; it is faced with new obstacles, which may be self-created. The article analyzes from a participant’s perspective the development of the New Left in the U.S., France and West Germany as it tried to articulate what is dubbed the "unknown dimension" of Marx’s theoretical project.